The Relationship Between Diet and Physical Activity and the Incidence of Obesity Among Students - Indriyana, Nabilah; Betty Yosephin Simanjuntak; Wahyudi, Anang (poltekkes kemenkes mataram, 2025)
Adolescents are in the age group of 10-18 years, need to prepare for adulthood and improve their health among malnutrition. Obesity is a condition where body fat is more than it should be. This situation can be caused by poor diet and lack of physical activity. The purpose of this study was to determine the relationship of diet and physical activity to the incidence of obesity in adolescents 16-17 years at High school Bengkulu City. This research is a quantitative research with cross sectional approach. This research was conducted at SMA Negeri 7 Bengkulu City. A sample of 81 students was obtained using random sampling technique. Diet was collected by instrument, with Eating Behavior Patterns Questionnaire (EBPQ), Physical activity using Physical Activity Questionnaire - Adolescent (PAQ-A). Measurement of body weight and height to determine IMT/U.Obtained students with a good diet of (80%), while physical activity is sufficient as much as (84%). The chi-square results show that there is a relationship between diet and obesity with a p-value (p=0.003) and there is a relationship between physical activity and obesity with a p-value (p=0.005).Concluded that diet and physical activity can affect the incidence of obesity in adolescents 16-17 years at High School Bengkulu City